MODERNIZED SEWING MACHINE BOBBIN CAP HOOK THREAD TENSION REGULATOR - Mukhamedjanova, Sabrina (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract. The article presents a modernized regulator of shuttle thread tension in sewing machines. The scheme of the new effective constructive scheme and the principle of operation of the shuttle thread tension regulator is developed.